Effects of Psidium Guajava Leaves Extract on the Viability of Echinococcus Granulosus Protoscolices in Vitro and in Vivo - Al-Arabi, Fadel Y. S.; Ali, Aidah M.; Omar, Gozif Mohammed N.; Mehdi, Mansour Abdulnabi H.; Mohsen, Mohammed; Farooqui, Mazahar; Pradhan, Vidya (Iraqi Journal of Science, 2022)
Echinococcosis is a common parasitic disease in humans and ruminants; it is considered as a health and economic problem in most parts of the world. The present study aims to evaluate the in vitro and in vivo scolicidal effects of Psidium guajava extracts on the protoscolices from hydatid cysts of Echinococcus granulosus. Protoscolices were aseptically aspirated from the livers of naturally infected sheep. Various concentrations of the extract were used for 6-48hrs. Eosin staining (0.1%) was used to determine the viability of protoscolices. The findings showed that the extract at the concentrations of 100 mg/ml killed 100% protoscolices after 48 hrs. However, the concentrations of 75 and 50 mg/ml were not effective in killing the protoscolices after 48 hrs. of exposure. The results of this investigation demonstrated that P. guajava could be used as a natural source for the production of new scolicidal agents.